Experimental analysis of early periprosthetic femoral fractures with uncemented straight hip stems. (January 2022) - Saemann, Michael; Darowski, Martin; Hennicke, Nina S.; Bader, Rainer; Sander, Manuela; Kluess, Daniel
Abstract: Background: The periprosthetic femoral fracture is one of the most severe complications after total hip arthroplasty and is associated with an increased mortality. The underlying causes and the patient- and implant-specific risk factors of periprosthetic femoral fractures remain insufficiently understood. The aim of this study was to gain a more profound understanding of the underlying fracture mechanisms and to provide experimental datasets for validation of computational models. Methods: Six cadaveric femurs were implanted with straight hip stems (Zweymueller design) and loaded until fracture reproducing the clinically relevant load cases stumbling and sideways fall. Displacements and the strain distribution on the surface of the femurs and implants, as well as the fracture load and implant subsidence were measured. Findings: For the load case stumbling the mean fracture load was 6743 N and two different mechanisms leading to fracture could be identified: high subsidence with low femoral bending and small subsidence with high femoral bending. For the load case sideways fall the mean fracture load was 1757 N and both tested femurs fractured due to a rotation of the hip stem around its own axis. The detailed datasets provided by this study can be used in future computational models. Interpretation: We demonstrated that the underlying fracture mechanisms of periprosthetic femoral fractures can be fundamentally different in the load case stumbling. The seating and exact position of the hip stem in the femur may correlate with implant subsidence and therefore lead to different types of fracture mechanisms resulting in different patient-specific fracture risks. Highlights: Early periprosthetic femoral fractures were experimentally reproduced. Measurement of displacements, strains, stresses, fracture loads and subsidence. Two fundamentally different fracture mechanisms could be observed during stumbling.